Efficacy and Safety of Jiawei Suanzaoren Decoction Combined with Lorazepam for Chronic Insomnia: A Parallel-Group Randomized Controlled Trial. (8th February 2020) - Song, Ming-Fen; Chen, Li-Qiong; Shao, Qiong-Yan; Hu, Lin-Lin; Liu, Wen-Juan; Zhang, Yong-Hua
Abstract : Background . Chronic insomnia is a major public health problem, but there are limited effective therapies. Jiawei Suanzaoren Decoction (JW-SZRD) has been used as an alternative option for treating insomnia. This study aimed to investigate the long-term efficacy and safety of JW-SZRD in combination with lorazepam for chronic insomnia. Methods . A total of 207 participants were analyzed in this study. The treatment group (TG) received JW-SZRD and lorazepam orally, and the control group (CG) received lorazepam alone. The Insomnia Severity Index (ISI), the Self-Rating Depression Scale (SDS), the Self-Rating Anxiety Scale (SAS), and the Somatic Self-rating Scale (SSS) were evaluated at baseline, weeks 4, 8, and 12. The MOS 36-item Short Form Health Survey (SF-36) was assessed at baseline and week 12. Adverse effects (AEs) were evaluated by the Treatment Emergent Symptom Scale (TESS). Results . Both TG and CG showed obvious improvements in the sleep onset latency (SOL) (P = 0.001 and 0.005) and total sleep time (TST) (P = 0.0001 and 0.001). However, TG was more effective than CG at weeks 8 (P = 0.02 for SOL, P = 0.008 for TST) and 12 (P = 0.03 for SOL, P = 0.04 for TST), especially in shortening SOL (Cohen's d = 1.28). The ISI reduction rate in TG was higher than that in CG at weeks 4, 8, and 12 (P = 0.008, 0.001 and 0.001). After treatment, TG had lower SAS scores (P = 0.0001, 0.007), less somatic symptoms (P < 0.05 or 0.01), higher SF-36 scores (P < 0.05 or 0.01), better compliance (P = 0.0001 ), and less adverse effects (P < 0.05 or 0.01) than those in CG. Conclusion . The combination of JW-SZRD with lorazepam can significantly improve sleep quality with fewer AEs. It is an effective treatment and superior to lorazepam alone for chronic insomnia.